1992
DOI: 10.1148/radiology.182.2.1732945
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary metastatic nodules: CT-pathologic correlation.

Abstract: To elucidate the characteristics of pulmonary metastatic nodules on high-resolution computed tomographic (HRCT) scans, a correlative computed tomographic (CT)-pathologic study was performed with five human lungs after autopsy. The relationship of metastatic nodules to pulmonary vessels was studied with HRCT scans, radiographs of the specimen, and stereomicroscopic study in 264 nodules 0.6-9.0 mm in diameter. On radiographs and stereomicroscopic images, 190 small nodules (less than 3 mm in diameter) were in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 0 publications
1
18
0
2
Order By: Relevance
“…Ill-defined discrete nodules of varying sizes with no relationship to lobular structures and interlobular septa as per Murata et al, were seen in one case with diffuse hematogeneous metastases to lung fields. 20 Cystic lesions of varying sizes were present in patient with Langerhans Cell Histiocytosis (LCH) and Lymphangioleiomyomatosis. In LCH, relative sparing of the bases was noted on HRCT whereas a more diffuse pattern of spread was seen in Lymphangioleiomyomatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ill-defined discrete nodules of varying sizes with no relationship to lobular structures and interlobular septa as per Murata et al, were seen in one case with diffuse hematogeneous metastases to lung fields. 20 Cystic lesions of varying sizes were present in patient with Langerhans Cell Histiocytosis (LCH) and Lymphangioleiomyomatosis. In LCH, relative sparing of the bases was noted on HRCT whereas a more diffuse pattern of spread was seen in Lymphangioleiomyomatosis.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this report is to present one of such case with feeding vessel sign that occurs in pulmonary metastasis 10 in a patient with a history of previously diagnosed melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…In a high-resolution CT (HRCT) study by Milne and Zerhouni [44], it was present in 75% of metastatic pulmonary nodules. On the other hand, in pathological samples, Murata et al [42] showed that the mass-vessel sign was not detectable, presumably because the vessels supplying the lesions are too small to be visualised by HRCT, whereas it appears in only 27% of cases of larger metastatic lesions (with a diameter >3 mm).…”
mentioning
confidence: 99%
“…This distribution occurs because the neoplastic cells reach the lungs through the bloodstream but can also cross the endothelium of the arterioles and capillaries and distribute within the perivascular tissues [41]. On pathological sections, Murata et al [42] studied the relationship between pulmonary metastases <3 mm in diameter and centrilobular structures, reporting that only about 12% of pulmonary metastases were centrilobular, with about 68% being located between the centrilobular structures and the interlobular septa and 20% at the level of the interlobular septa. Our MIP and VR reconstructions yielded comparable results, as 65% of nodules were centrilobular and 35% interlobular.…”
mentioning
confidence: 99%
See 1 more Smart Citation